1976
DOI: 10.1161/01.res.39.3.433
|View full text |Cite
|
Sign up to set email alerts
|

Cell permeability, sodium transport, and the hypertensive process in the rat.

Abstract: The tail artery of the spontaneously hypertensive rat (SHR) (Carworth Farms), excised rapidly and immersed immediately in cold (2 degrees C) Li-substituted physiologic salt solution (LiPSS), continues to exchange cell Na+ and K+ for Li+, this exchange is negligible to the control (Carworth Farms normotensive) CFN). In the incubated artery at 37 degrees C, when the vascular smooth muscle cell is slack, the leakiness of the cell membrane in the SHR is more than offset by increased Na+ pumping activity, so that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 24 publications
4
37
0
Order By: Relevance
“…These data suggest that, for any level of total cell Na + , Na + -K + pump activity is higher in arterial tissue from the DOCA-salt hypertensive rats. Friedman et al 11 ' ie have demonstrated that there is a slightly increased exchange of Li + for cell Na + and K + in tail artery from DOCA-salt hypertensive rats. Since we used a Li + substitution method to estimate cell Na + , increased Na + -Li + exchange might account for a portion of the shift of the DOCA-curve.…”
Section: -47mentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that, for any level of total cell Na + , Na + -K + pump activity is higher in arterial tissue from the DOCA-salt hypertensive rats. Friedman et al 11 ' ie have demonstrated that there is a slightly increased exchange of Li + for cell Na + and K + in tail artery from DOCA-salt hypertensive rats. Since we used a Li + substitution method to estimate cell Na + , increased Na + -Li + exchange might account for a portion of the shift of the DOCA-curve.…”
Section: -47mentioning
confidence: 99%
“…410 As measured by different in vitro techniques, increased active transport of Na + and K + has been observed in arterial smooth muscle from spontaneously hypertensive rats, 11 " 1 ' from Dahl salt-sensitive hypertensive rats, 17 ' 18 and from DOCA-salt hypertensive rats. 11 ' """ It has been suggested that these increases in vascular Na + -K + pump activity in hypertension result from elevations in the concentration of intracellular Na + , associated with increased passive permeability of the cell membrane to Na + . M " M Overbeck et al, 18 however, suggested that additional factors may be involved.…”
mentioning
confidence: 99%
“…Evidence has been presented indicating that this pump inhibitor is increased in the plasma of some forms of hypertension, 46 -47 yet in vitro observations indicate that this pump activity is increased instead of decreased in hypertension. 48 - 49 We have compared pump activity in vivo in DOCA hypertensive and normotensive pigs with rubidium clearance from the plasma used as an index of pump activity levels (L. Vo and D.F. Bohr, unpublished observation).…”
Section: Humoral Agentsmentioning
confidence: 99%
“…8 -'•• 17 The strips were incubated at 37°C for 3 hours in a physiologic or modified solution containing "Na (20-30 / 24 Na took place at 1°C, and the washout was begun at 1°C as the tissues were passed through a series of vigorously gassed solutions that contained the desired [K] o . This technique provides a rapid dilution of the isotope into the nonlabeled solution, thus allowing efflux components with low temperature coefficients to be readily separated from those that are highly sensitive.…”
Section: Isotope Fluxesmentioning
confidence: 99%
“…The wall thickness for the aorta from DOCA hypertensives is 0.19 cm 8 , which results in a diffusion path, 1, of 0.0095 cm. The ratio R of cellular to extracellular Na in K-loaded aorta is 0.02, and the maximum rate constant associated with this component is 0.445 min" 1 (table 1) or 0.74 X 10 l sec' 1 .…”
mentioning
confidence: 99%